Exploring Corporate Social Responsibility in Increasing Gender Diversity in the Banking Sector: Bibliometric Analysis - Fahri, Hamnatul Millah; Kholmi, Masiyah (Universitas Pamulang, 2025)
Gender diversity in the banking sector is increasingly becoming an important issue, especially in the context of Corporate Social Responsibility (CSR). This study aims to explore the role of CSR in increasing gender diversity in the banking sector and its impact on company performance. The method used is a bibliometric analysis that analyzes publications related to CSR and gender diversity from 2019 to 2024. Data obtained from the Scopus database, with the keyword